Regulation of microglia function by neural stem cells - de Almeida, Monique M. A.; Goodkey, Kara; Voronova, Anastassia (Frontiers in Cellular Neuroscience, 2023)
Neural stem and precursor cells (NPCs) build and regenerate the central nervous system (CNS) by maintaining their pool (self-renewal) and differentiating into neurons, astrocytes, and oligodendrocytes (multipotency) throughout life. This has inspired research into pro-regenerative therapies that utilize transplantation of exogenous NPCs or recruitment of endogenous adult NPCs for CNS regeneration and repair. Recent advances in single-cell RNA sequencing and other “omics” have revealed that NPCs express not just traditional progenitor-related genes, but also genes involved in immune function. Here, we review how NPCs exert immunomodulatory function by regulating the biology of microglia, immune cells that are present in NPC niches and throughout the CNS. We discuss the role of transplanted and endogenous NPCs in regulating microglia fates, such as survival, proliferation, migration and activation, in the developing, injured and degenerating CNS. We also provide a literature review on NPC-specific mediators that are responsible for modulating microglia biology. Our review highlights the immunomodulatory properties of NPCs and the significance of these findings in the context of designing pro-regenerative therapies for degenerating and diseased CNS.